Neuraxial anesthesia for non-neurological emergency surgery in a patient with acute ischemic stroke: a case report - Asish Subedi; Ashok Gautam (International Journal of Emergency Medicine, 2024)
Abstract Background The recent guidelines recommend delaying elective non-neurological surgery after an index stroke, but there is a lack of consensus regarding emergency surgery in patients with a recent stroke. Impaired cerebral autoregulation and altered baroreceptor function elevate the risk of recurrent stroke in this group. Moreover, the impact of anesthesia type (general vs. regional) for non-cardiovascular, non-neurological surgery in patients with an index stroke remains inconclusive. Case presentation A 67-year-old male with an acute mild ischemic stroke underwent emergency surgery for an obstructed right-sided direct inguinal hernia under combined spinal-epidural anesthesia. Pre-operative assessment showed stable hemodynamics, and perioperative measures were taken to ensure stable blood pressure. Neuraxial anesthesia was employed successfully, and the patient remained hemodynamically stable throughout the surgery and postoperative period. No neurological deficits were observed post-surgery, and follow-up up to 3 months revealed no cognitive impairment or neurological decline. Conclusions Neuraxial anesthesia can be considered for patients with acute mild strokes requiring urgent non-neurological surgery, provided they are hemodynamically stable and without coagulopathy. However, the choice of anesthesia should be individualized based on factors such as neurological status, stroke severity, coagulation, and existing disabilities. This case highlights the importance of a personalized approach to anesthesia in emergency surgery for stroke patients.